Practical implications of using real-world evidence (RWE) in comparative effectiveness research: learnings from IMI-GetReal. (September 2017) - Makady, Amr; Stegenga, Heather; Ciaglia, Antonio; Debray, Thomas PA; Lees, Michael; Happich, Michael; Ryll, Bettina; Abrams, Keith; Thwaites, Rob; Garner, Sarah; Jonsson, Páll; Goettsch, Wim; et al.
In light of increasing attention towards the use of real-world evidence (RWE) in decision making in recent years, this commentary aims to reflect on the experiences gained in accessing and using RWE for comparative effectiveness research as a part of the Innovative Medicines Initiative GetReal Consortium and discuss their implications for RWE use in decision-making.